Cross-Talk of the CNS With Immune Cells and Functions in Health and Disease - Matejuk, Agata; Vandenbark, Arthur A.; Offner, Halina (Frontiers in Neurology, 2021)
The immune system's role is much more than merely recognizing self versus non-self and involves maintaining homeostasis and integrity of the organism starting from early development to ensure proper organ function later in life. Unlike other systems, the Central Nervous System (CNS) is separated from the peripheral immune machinery that for decades has been envisioned almost entirely as detrimental to the nervous system. New research changes this view and shows that blood-borne immune cells (both adaptive and innate) can provide homeostatic support to the CNS via neuroimmune communication. Neurodegeneration is mostly viewed through the lens of the resident brain immune populations with little attention to peripheral circulation. For example, cognition declines with impairment of peripheral adaptive immunity but not with the removal of microglia. Therapeutic failures of agents targeting the neuroinflammation framework (inhibiting immune response), especially in neurodegenerative disorders, call for a reconsideration of immune response contributions. It is crucial to understand cross-talk between the CNS and the immune system in health and disease to decipher neurodestructive and neuroprotective immune mechanisms for more efficient therapeutic strategies.